THE SIGNIFICANCE OF PHYSICS IN AGRICULTURE - Чори Холиқович Тошпўлатов (American Journals, 2023)
The article briefly describes the place and role of physics in agriculture.
Keywords: agriculture, physics, plants, land, nature, experience